CFD Prediction of B-Series Propeller Performance in Open Water - Fitriadhy, Ahmad; Adam, Nur Amira; Quah, C.J.; Koto, Jaswar; Mahmuddin, Faisal (CFD Letters, 2021)
In presence of hydrodynamics interactions between propeller and velocity fields, it may lead to inaccurate prediction of the propeller’s quantities such as thrust, torque, and its efficiency. This paper presents a Computational Fluid Dynamics (CFD) simulation approach to predict the thrust (KT), torque (KQ) and efficiency (?) coefficients in open-water condition. The scale model of propeller with various blade numbers (Z) have been appropriately taken into account within the range of advance number 0.1?J?1.05. Here, B-series model propeller has been employed in computational simulation. In general, the results revealed that the subsequent increase of blade numbers has been proportional with the magnitude of KT and KQ of the propeller. However, it was inversely proportional to the propeller efficiency coefficient (?); where the highest efficiency value was 89% occurred at Z=3. This CFD simulation provides a preliminary prediction of the propeller characteristics.